Improving hospital formulary drug decision making with multi-criteria decision analysis (MCDA): case study from a national government hospital in Indonesia - Kristin, Erna; Bustami, Mursyid; Pinzon, Rizaldy Taslim; Alfi Yasmina; Susanto, Agnes; Febrinasari, Ratih Puspita (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2023)
This study aimed to look at the applicability of the multi-criteria decision analysis (MCDA) framework to improve hospital formulary drug decision-making. The case study method was used to investigate MCDA implementation in the National Brain Center Hospital Jakarta, Indonesia. A two stage-workshop was held on October 29th, 2019 and 5 February 5th, 2020, where participants conducted a hands-on experience in applying MCDA for selecting off-patent pharmaceuticals (OPPs) for the hospital formulary. The results of the workshop created awareness of MCDA that can be beneficial in transparently selecting OPP, which is not based only on price while involving multiple stakeholders. As a follow-up, MCDA was used during the drug selection process for the National Brain Center Hospital formulary in 2021 with criteria in accordance with the workshops, namely: 1) equivalence with the reference (originator) product; 2) real-world clinical or economic outcomes; 3) quality assurance; 4) reliability of drug supply; 5) stability and drug formulation; 6) pharmacovigilance, and 7) price advantages. In conclusion, the MCDA method can be implemented with customized criteria and weighting based on hospital needs to help with drug selection for the hospital formularies.